Utility of GeneXpert Mycobacterium tuberculosis/rifampicin assay in smear-negative pulmonary tuberculosis - Javeriya Mohammadi; Gummadi Anish Reddy; Alamelu Haran (Wolters Kluwer Medknow Publications, 2021)
Background: Tuberculosis (TB) remains one of the world's deadliest communicable diseases. An alarming rise in the incidence of Mycobacterium tuberculosis (MTB) has prompted the need for rapid diagnostic techniques. Despite low sensitivity in MTB detection, sputum microscopy remains the main diagnostic method, especially in resource-limited settings. Mycobacterial culture is the gold standard method for TB diagnosis; however, the use in clinical practice is limited due to longer time, biosafety requirements, and high cost. In December 2010, the World Health Organization (WHO) 1st endorsed the usage of Xpert MTB/rifampicin (RIF) assay. The WHO recommends that GeneXpert test could be used as a follow on test to microscopy, especially in smear-negative specimens. Objectives: To assess percentage of Tuberculosis cases and Multi Drug Resistant (MDR) case detection at diagnosis using Xpert MTB/RIF assay in smear-negative pulmonary cases. Materials and Methodology: Detailed relevant clinical history and examination were carried out for 105 pulmonary TB suspect patients. Sputum acid-fast bacilli smear two samples and human immunodeficiency virus status were checked under RNTCP; chest X-ray PA view was done. Smear-negative patients were subjected to bronchoscopy and bronchoalveolar lavage (BAL)/bronchial washing. BAL/Bronchial washing was tested for GeneXpert. Interpretation and Conclusion: MTB was detected in 21 (20%) samples out of 105 samples and RIF resistance was detected in 1 (1%) sample. Most common chest x-ray abnormalities were cavity (33.3%) and consolidation (33.3%). 8 cases (38.1%) among Gene xpert positives had past history of Tuberculosis. Comorbidities were found in 5 cases (23.8%) among Gene Xpert positives. The present study concludes that using standard clinical assessment for selection, five patients need to be tested to detect one case of smear-negative TB. Smear-negative patients could benefit from Xpert, particularly in areas where no culture is available.